2019
DOI: 10.1111/anae.14851
|View full text |Cite
|
Sign up to set email alerts
|

An initial evaluation of the effect of a novel regional block needle with tip‐tracking technology on the novice performance of cadaveric ultrasound‐guided sciatic nerve block

Abstract: Summary Visibility of the needle tip is difficult to maintain during ultrasound‐guided nerve block. A new needle has been developed that incorporates a piezo element 2–2.3 mm from the tip, activated by ultrasound. The electrical signal manifests as a coloured circle surrounding the needle tip, and allows real‐time tracking. We hypothesised that novice regional anaesthetists would perform nerve block better with the tracker turned on rather than off. Our primary objective was to evaluate the new needle by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…McLeod et al showed that the Onvision tracking technology can improve the performance of unexperienced anesthesiologists when conducting in-plane sciatic blocks in a cadaver study. 13 Accordingly, McVicar et al showed a significant improvement of technical needling skills of novice trainees in an ex vivo model when using an electromagnetic needle tracking system. 14 Since our present study was performed in healthy volunteers, it was considered as ethically questionable and inappropriate to involve less experienced colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McLeod et al showed that the Onvision tracking technology can improve the performance of unexperienced anesthesiologists when conducting in-plane sciatic blocks in a cadaver study. 13 Accordingly, McVicar et al showed a significant improvement of technical needling skills of novice trainees in an ex vivo model when using an electromagnetic needle tracking system. 14 Since our present study was performed in healthy volunteers, it was considered as ethically questionable and inappropriate to involve less experienced colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…19 While tofu, gelatin or muscle tissue phantoms provide acceptable feel for tissue and ultrasound attenuation, cadavers are considered as anatomically most relevant. 13 However, block success, failure rates, or adverse events must be estimated indirectly in these models. 3 As a first in human testing of the Onvision needle tip tracking technology, we considered a volunteer trial appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Forty subjects then conducted sciatic block on one out of three soft embalmed cadavers ( We used a within-subjects experimental model: each subject was exposed equally to the activated or nonactivated tracker needle and randomised by computer software to one out of two sequences (Fig. 1 We used data from our previous study [7] to power the current study. In that, there was a median difference of 2.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has sought to improve training by using a soft embalmed Thiel cadaver simulator [5], application of mastery learning techniques [4], quantitative measurement of performance using validated checklists of steps and errors [6] and eye-tracking analysis [3,6,7]. The most difficult tasks encountered by trainees were viewing the needle tip at all times, recognition of needle-nerve contact and detection of intraneural injection [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation